HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG COVID-19 DENGAN PERILAKU VAKSINASI DI WILAYAH KERJA PUSKESMAS TELAGA DEWA KOTA BENGKULU 2021: HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG COVID-19 DENGAN PERILAKU VAKSINASI DI WILAYAH KERJA PUSKESMAS TELAGA DEWA KOTA BENGKULU 2021 - Nadhyifa; Eka Nugraheni, Diah; Yuniarti (Poltekkes Kemenkes Bengkulu, 2024)
Abstract : According to the World Health Organization (WHO) Since the end of December 2019, in Wuhan, People's Republic of China, an outbreak caused by one type of betacoronavirus has emerged. The government has made various efforts to prevent COVID-19, especially for pregnant women. One of them is vaccination.study aims to determine the relationship between knowledge and attitudes of pregnant women in the third trimester to the behaviorof COVID-19 vaccination at the Telaga Dewa Health Center, Bengkulu City in 2021. This type of research is a cross sectional approach. The population in this study were pregnant women in the third trimester in the working area of ​​the TelagaDewa Health Center. The total population of pregnant women in the Telaga Dewa Health Center Work Area is 411 pregnant women in the third trimester, with sampling using the Lemeshow formula so that 78 respondents will be examined. The research instrument used a questionnaire. Data analysis using chi square. The results of the chi square showed a value of 0.033 (<0.05) meaning that there was a significant relationship between knowledge and vaccination behavior of pregnant women.test analysis chi square obtained a value of 0.010 (<0.05). From the results above, it is known that there is a significant relationship between attitudes and vaccination behavior of pregnant women. It is hoped that they can seek to increase knowledge about COVID-19 and vaccination both through the internet and take part in health education so that they can carry out vaccinations in order to reduce the risk of being infected with COVID-19. Keywords: Covid-19, Vaccination of pregnant women, Knowledge, Attitude